The Implementation of Pancasila Values in Civics Learning in the Digital Era - Princessa Dinda Oktaviana; Fathurrohman; Sekar Purbarini Kawuryan; Bambang Saptono (MIMBAR PGSD Undiksha, 2023)
Pancasila must be actualized in various areas of life, one of which is education. Objective this research to review implementation, obstacles, and challenges in implementing Pancasila values in Indonesian Civics learning in the digital era. The data collection techniques used were observation and interviews. Test the validity of the data using source triangulation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The research results show that students have understood the form of understanding Pancasila values in the digital era.The values of Pancasila are implemented for students, including efforts to build student character, emphasizing the learning process based on living values by utilizing developing technological advances, making learning interactive, linking Pancasila values with technological developments, discussing contemporary issues relevant to Pancasila. The Pancasila values that have been implemented refer to the Pancasila principles.Obstacles in implementing Pancasila values include low awareness and lack of awareness filtering of information, internet connection problems, device limitations, difficulty in motivating students, lack of supervision, lack of experience with technology,absence of study friends, deviation from Pancasila values, and differences in student abilities.The challenge is lack of social interaction between students, limited scope, limited direct experience, minimal control over information, different technological capabilities, and the presence of globalization.